2000
DOI: 10.1021/ja993653s
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of CVD Metallization Processes:  Reactions of Rhodium and Platinum β-Diketonate Complexes on Copper Surfaces

Abstract: The hexafluoroacetylacetonate complexes Rh(hfac)(C 2 H 4 ) 2 and Pt(hfac) 2 are known to serve as chemical vapor deposition precursors to Rh and Pt thin films. In the absence of a reducing carrier gas, the depositions are surface-selective and occur preferentially on copper, but under these conditions, the metallization processes are unexpectedly inefficient relative to the rapid deposition of Pd on Cu seen for the palladium analogue Pd(hfac) 2 . Mechanistic studies of the reactions of Rh(hfac)(C 2 H 4 ) 2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Bond lengths 3 X, but somewhat surprisingly, to the best of our knowledge, this is the first pyrazolate complex of this kind. The compound crystallizes in the space group C2 with four molecules per unit cell.…”
Section: Table 2 Selected Bond Lengths (å) and Angles (°) Formentioning
confidence: 75%
See 4 more Smart Citations
“…Bond lengths 3 X, but somewhat surprisingly, to the best of our knowledge, this is the first pyrazolate complex of this kind. The compound crystallizes in the space group C2 with four molecules per unit cell.…”
Section: Table 2 Selected Bond Lengths (å) and Angles (°) Formentioning
confidence: 75%
“…CVD processes can also allow for the selective growth of films that have good step coverage compared with traditional techniques such as PVD. [1][2][3] Thin films of rhodium are used as electrical contacts, 4,5 reflective coatings, 6,7 catalysis, 8,9 and wearresistant coatings for extreme conditions. 2,10 Previous studies have focused on volatile compounds which feature traditional organometallic ligands such as CO, C 2 H 4 , C 5 H 5 , and fluorinated hydrocarbons such as trifluoroacetylacetonate and it has been shown that film quality is dependent on the precursor used.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations